Synthesis and characterization of lacuo3 and cecuo3 perovskites and yttrium or potassium-promoted perovskite for selectivity, longevity and kinetic studies of ethanol dry reforming. - Attili, Ramkiran (2024)
Ethanol and carbon dioxide are potential, sustainable feedstocks for syngas productions via ethanol dry reforming (EDR) reaction. Copper is one of the active, non-noble catalysts for this reaction, but prone to deactivation due to sintering and carbon deposition at high reaction temperatures. A strong and thermally stable support of perovskite structure from lanthanum or cerium and oxidating agent like yttrium or potassium are potential solution for the Cu-based catalyst problems. Therefore, the objectives of this study were to prepare and investigate the physicochemical properties of the catalysts, evaluate their selectivity and longevity, assess conversions based on various feed ratios and reaction temperatures, and determine kinetic parameters in the EDR reaction. The citric sol-gel method was employed to prepare the catalysts based on the perovskite compositions denoted as A1- xBxCuO3, where x was varied from 0 to 1 within 0.25 interval. A represents lanthanum or cerium, and B is yttrium or potassium. The reduced and spent catalysts were characterized using BET, XRD, TPR, FTIR, SEM, Raman Spectroscopy, and TEM methods. The catalyst activity in the EDR reaction was tested in a flow tubular reactor system at reaction temperatures ranging from 948 to 1073 K and CO2:C2H5OH ratios from 2.5 to 1 under atmospheric pressure, with partial pressures of CO2 and ethanol varying from 20 to 70 kPa. The promotion effect was investigated stepwise, starting with the support of A (lanthanum or cerium) without B (yttrium or potassium). Notably, LaCuO3 exhibited better characteristics of surface area 60 times larger than CeCuO3 despite of a drop by 50% after the EDR reaction, more carbon nanofilament in TEM and SEM images, greater crystallinity of perovskite and metal oxides in the XRD results before and after the reaction. Raman spectra also confirmed the carbon presence more in the CeCuO3 catalysts. Both catalysts exhibited two reduction temperatures, with the latter being higher. Thus, LaCuO3 appeared more active, resulting in higher conversion, product yield, and an elevated H2/CO ratio during the EDR test. Specifically, the CO2 and ethanol conversions increased to 86% and 30%, respectively, as the reaction temperature rose from 923 to 1073 K. During the EDR reaction, the H2/CO ratio always remained a higher value than unity due to the occurrence of the ethanol dehydrogenation reaction, which is suitable for F-T synthesis. The promotion of yttrium and potassium loading higher than 25% onto the perovskite catalysts did not improve the EDR reaction performance. La0.75Y0.25CuO3 exhibited the highest catalytic activity, equivalent to LaCuO3, and showed resistance to coke deposition for 72 h on stream at a stoichiometric ratio and 1023 K. These results are better than those achieved with cobalt-based catalyst and zirconiabased catalyst. Additionally, La0.75Y0.25CuO3 had a lower carbon composition in EDX result compared to LaCuO3. The Langmuir-Hinshelwood rate expression suggests that both reactants (C2H5OH and CO2) are associatively adsorbed on a single site catalyst, with a corresponding activation energy of approximately 102.24 kJ mol-1 on La0.75Y0.25CuO3. Overall, LaCuO3 and La0.75Y0.25CuO3 are the best perovskite catalysts prepared that had low carbon deposition, longevity and high activity in the EDR reaction.